Low-phytate wholegrain bread instead of high-phytate wholegrain bread in a total diet context did not improve iron status of healthy Swedish females: a 12-week, randomized, parallel-design intervention study - Hoppe, Michael (Eur J Nutr, 2018)
PURPOSE: To investigate the effects of eating wholegrain rye bread with high or low amounts of phytate on iron status in women under free-living conditions. METHODS: In this 12-week, randomized, parallel-design intervention study, 102 females were allocated into two groups, a high-phytate-bread group or a low-phytate-bread group. These two groups were administered: 200 g of blanched wholegrain rye bread/day, or 200 g dephytinized wholegrain rye bread/day. The bread was administered in addition to their habitual daily diet. Iron status biomarkers and plasma alkylresorcinols were analyzed at baseline and post-intervention. RESULTS: Fifty-five females completed the study. In the high-phytate-bread group (n = 31) there was no change in any of the iron status biomarkers after 12 weeks of intervention (p > 0.05). In the low-phytate bread group (n = 24) there were significant decreases in both ferritin (mean = 12%; from 32 ± 7 to 27 ± 6 µg/L, geometric mean ± SEM, p < 0.018) and total body iron (mean = 12%; from 6.9 ± 1.4 to 5.4 ± 1.1 mg/kg, p < 0.035). Plasma alkylresorcinols indicated that most subjects complied with the intervention. CONCLUSIONS: In Swedish females of reproductive age, 12 weeks of high-phytate wholegrain bread consumption had no effect on iron status. However, consumption of low-phytate wholegrain bread for 12 weeks resulted in a reduction of markers of iron status. Although single-meal studies clearly show an increase in iron bioavailability from dephytinization of cereals, medium-term consumption of reduced phytate bread under free-living conditions suggests that this strategy does not work to improve iron status in healthy women of reproductive age.